Traveling Thrombus in the Right Atrium: Is It the Final Destination?. (9th August 2012) - Bhargava, Maneesh; Dincer, Erhan
Abstract : Right heart thrombus is rare in structurally normal heart. Here, we report a 74-year-old man with a right atrial thrombus who presented with shortness of breath.